Level set of the asymptotic rate of convergence of the method of steepest descent - Zhuk , P. F.; Жук, Петро Федорович; Жук, П. Ф. (Institute of Mathematics, NAS of Ukraine, 2022)
UDC 519.61 The asymptotic rate of convergence of the steepest descent method is considered as a function of the initial approximation. In this work, we study the set of the level of this speed, i.e. the set of initial approximations for which it takes a given value. A method for constructing this set is proposed and its connected components are found.